Neutrophil-to-lymphocyte ratio in pediatric acute appendicitis - Stanković Nikola; Stanojević Ivan; Đorđević Dragan; Kostić Zoran; Udovičić Ivo; Miličković Maja; Savić Đorđe; Grujić Blagoje; Đuričić Slaviša; Šurbatović Maja (Vojnosanitetski Pregled)
Background/Aim. Acute appendicitis (AA) is the most frequent emergency and appendectomy is the most frequent abdominal operation in the pediatric surgery. Diagnosis of AA in children is more difficult due to a lack of cooperation and poor clinical history data, leading to significant number of misdiagnostic cases. Our aim was to explore whether neutrophil to lymphocyte ratio (NLR) may be useful in diagnosis and follow-up of AA in children. Methods. Prospective investigation of NLR values in 129 consecutive patients admitted to the Mother and Child Healthcare Institute of Serbia and referred for surgery due to AA was performed. According to the pathohistological findings, patients were divided into 3 groups: normal/early, uncomplicated (phlegmonous) and complicated (gangrenous or/and perforated) AA. Laboratory analysis was done preoperativly and on the 1st and the 3rd postoperative days. Results. Statistically significant differences of NLR values were found in the different time points in total of patients and per groups. Some statistically significant differences of NLR values among histopathological groups were recorded. Investigations of correlation of NLR and other laboratory and clinical parameters showed strong positive correlation between NLR and C-reactive protein postoperatively and between NLR and Pediatric Appendicitis Score (PAS) preoperatively. Strong negative correlation with preoperative symptoms duration (PSD) were also present. Optimal cutoff NLR value between negative and positive appendectomies was 6.14. Conclusion. NLR provides well monitoring of progression of AA in children and, its cutoff values may help in distinguishing the phases of AA. Because of that, NLR should be used in diagnosis of AA in children.